The contested nature of heritage in Grade 10 South African History textbooks: A case study (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Using the interpretivist paradigm and approached from a qualitative perspective, this case study produced data on three purposively selected contemporary South African history textbooks with regards to their representation of heritage. Lexicalisation, a form of Critical Discourse Analysis (CDA), was used as method to analyse the pre-generated data from the selected textbooks. In this Fairclough’s (2003) three dimensions of describing, interpreting, and explaining the text was followed. The study adopted a holistic approach to heritage as a conceptual framework whilst following social constructionism as the lens through which heritage was explored in the selected textbooks. The findings from this study concluded that although educational policy in the form of the National Curriculum Statement – NCSHistory clearly stipulates the expectations to be achieved from the teaching and learning of heritage at Grade 10 level, there are inconsistencies and contradictions at the level of implementation of the heritage outcome in the history textbooks. Key among the findings are the absence of representation of natural heritage, lack of clear conceptualisation of heritage, many diverse pedagogic approaches towards heritage depiction, a gender and race representation of heritage that suggests an inclination towards patriarchy and a desire to retain apartheid and colonial dogma respectively, and finally a confirmation of the tension in the heritage/history relationship.
Keywords: Heritage; History; Textbooks; Lexicalisation; CDA